Approach to repeat ablation of atrial fibrillation when the pulmonary veins are already isolated. (11th November 2019) - Chiocchini, Andrea; Verma, Atul
Abstract: In this article, we summarize our approach to a repeat ablation for persistent atrial fibrillation when the pulmonary veins are already isolated. We summarize the approach to posterior wall isolation, ablation of drivers of atrial fibrillation, and also ablation of incompletely ablated regions identified during sinus rhythm.